Efficacy and safety of tafluprost 0.0015% – retrospective analysis of real-world data from the Philippines - Tumbocon JA (Dove Medical Press, 2019)
Joseph Anthony Tumbocon,1,2 Anne Marie Macasaet11Eye Institute, St. Luke’s Medical Center, Quezon City, Philippines; 2Department of Ophthalmology, St. Luke’s College of Medicine, Quezon City, PhilippinesCorrespondence: Joseph Anthony TumboconEye Institute, St. Luke’s Medical Center, 279 E. Rodriguez Sr. Blvd., Quezon City 1102, PhilippinesTel +632 789 7700 Ext 7212Fax +632 789 7700 Ext 7212Email jatumbocon@gmail.comPurpose: To investigate the IOP lowering effect and safety of tafluprost 0.0015% in a routine clinical setting in the Philippines.Patients and methods: A retrospective review of glaucoma patients receiving tafluprost 0.0015% (BAK 0.001% preserved) with a minimum follow-up of 3 months was conducted. Main outcome measure was the mean IOP change at month 3. Secondary outcome measures included longitudinal IOP assessments and occurrence of any adverse events.Results: Three-hundred twenty-nine eyes of 177 patients with mean age 64.8 years were included and followed for mean 8.8 months. Most common diagnosis was primary open-angle glaucoma (POAG) (34.9%), followed by primary angle-closure (PAC) glaucoma post-laser iridotomy (24.0%), PAC post-laser iridotomy (15.5%), ocular hypertension (OHT)(14.6%), secondary glaucoma (6.7%), and normal-tension glaucoma (4.3%). Mean IOP change at month 3 was −6.18 mmHg (SD 4.06), a −26.37% reduction (p<0.001) and IOP reduction was sustained throughout the study period (p<0.001). Sub-group analysis of treatment naïve (n=203); add-on (n=53) and replacement therapy (n=73) showed a 3-month mean IOP reduction of −8.34 mmHg (SD 2.57, p<0.001) or –31.24%, −5.08 mmHg (SD 2.86, p<0.001) or –23.68%, and −1.00 mmHg (SD 3.08; p=0.007) or –6.31%, respectively. There was significant IOP reduction from baseline in both POAG/OHT sub-group and the PAC/PACG post-laser iridotomy with ≥90° open-angle sub-group (p<0.001), sustained up to month 12 post-treatment. However, there was no significant difference in the average absolute (mmHg) or proportional IOP change from baseline between the two sub-groups. Conjunctival hyperemia was the most common adverse reaction occurring in 15% of patients.Conclusion: Tafluprost was a safe and effective IOP-lowering treatment in this routine clinical setting.Keywords: tafluprost 0.0015%, primary open-angle glaucoma, IOP reduction